BL_GERICHTE 725 18 384/99 vom 12. Februar 2018 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht, vom 11. April 2019 (725 18 384/99) - BL Gerichte (2018)
Revision/Leistungen